Transcriptomic analysis of Corynebacterium glutamicum in the response to the toxicity of furfural present in lignocellulosic hydrolysates - Park, Hong-Sil; Um, Youngsoon; Sim, Sang Jun; Lee, Sang Yup; Woo, Han Min (Elsevier Applied Science, 2015)
Pretreatment of lignocellulosic biomass by acid hydrolysis generates growth inhibitors such as furfural, 5-hydroxymethylfurfural, and acetic acid. Among the inhibitors, furfural strongly inhibits cell growth, our objective was to identify the furfural stimulon of an amino acid producer Corynebacterium glutamicum using transcriptomic analysis. As a result, 182 up-regulated (2-fold) genes and 81 down-regulated (0.5-fold) genes were identified for all furfural stress conditions (6.5 mM, 13 mM, and 20 mM). Based on the functional categories of CoryneRegNet database, the furfural stimulon was related to genetic responses of oxidative stress, SOS responses, and anaerobic respiratory metabolism. To overcome the furfural toxicity, furfural-responsive efflux-like permease encoded by the cg1661 gene was overexpressed, resulting that the optical density at 600nm was 1.54-fold enhanced over the control at 12 h. This study provides alternative strategy of metabolic engineering for biological detoxification in addition to overexpression of NADH-dependent reductases. (C) 2014 Elsevier Ltd. All rights reserved.